2019
DOI: 10.1002/jcp.29223
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of lncRNA/miRNA/mRNA and their related functional networks during the osteogenic/odontogenic differentiation of dental pulp stem cells

Abstract: Dentin-pulp regeneration requires dental pulp stem cells (DPSCs), but the role of long noncoding RNAs (lncRNAs) during this process remains unclear. Here, we cultured human DPSCs in osteogenic/odontogenic medium for 14 days and analyzed cells via RNA-sequencing. The data were validated by quantitative reverse transcriptionpolymerase chain reaction and lncRNA-microRNA (miRNA)-messenger RNA (mRNA) networks were constructed to reveal the potential competing endogenous RNA regulatory role of lncRNAs. Kyoto Encyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 41 publications
(40 reference statements)
3
38
0
Order By: Relevance
“…In addition, miR-138, miR-31, miR-142, miR-148, and miR-637 could inhibit the expression of OSX (Zhang et al, 2012;Liu et al, 2020). Chen et al (2016) found that serum miR-30b-5p level was significantly down-regulated in postmenopausal women, and the results were consistent in the corresponding rat model.…”
Section: Other Mirnasmentioning
confidence: 61%
See 2 more Smart Citations
“…In addition, miR-138, miR-31, miR-142, miR-148, and miR-637 could inhibit the expression of OSX (Zhang et al, 2012;Liu et al, 2020). Chen et al (2016) found that serum miR-30b-5p level was significantly down-regulated in postmenopausal women, and the results were consistent in the corresponding rat model.…”
Section: Other Mirnasmentioning
confidence: 61%
“…Promote osteoblastic differentiation (Hassan et al, 2012) miR-143, miR-31 OSX Inhibit osteoblastic differentiation (Zhang et al, 2012;Li E. et al, 2014;Liu et al, 2020) miR-101, miR-132 PI3K/AKT/mTOR pathway Promote osteoblastic differentiation (Qi and Zhang, 2014) miR-17 TCF/Wnt pathway Inhibit osteoblastic differentiation (Liu et al, 2013) miR-216 PI3K/AKT pathway Promote osteoblastic differentiation (Xiao et al, 2016) miR-194 STAT1 Promote osteoblastic differentiation (Li et al, 2015) miR-96 EGFR signaling Promote osteoblastic differentiation (Yang et al, 2014) miR-23 MARK pathway Inhibit osteoblastic differentiation (Jiang et al, 2020) miR-375 RUNX2 Inhibit osteoblastic differentiation (Du et al, 2015) miR-153 BMPRII Inhibit osteoblastic differentiation (Cao et al, 2015) miR-124 DLX Inhibit osteoblastic differentiation MiR-125b OSX Inhibit osteoblastic differentiation (Chen et al, 2014) mTOR, mammalian target of rapamycin; SMAD1, SMAD Family Member 1; TGIF, transforming growth factor-β induced factor; BMP7, Bone morphogenetic protein 7; GSK3β, Glycogen synthase kinase-3β; c-Myc, MYC proto-oncogene; HMGA1, high mobility group A; PPARγ, peroxisome proliferator activated receptor γ; Spry, Sprouty; OSX, osterix; HDAC 5, histone deacetylase 5; HOXA2, Homeobox A 2; RUNX2, Runt-related transcription factor 2; DKK1, Dickkopf 1; DKK1, Dickkopf 2; Krm2, Kremen2; sFRP2, secreted frizzled-related protein 2; SOST, sclerostin; STAT1, signal transducer and activator of transcription 1; BMPRII, bone morphogenetic protein receptor II; DLX, distal-less homeobox gene.…”
Section: Smad5mentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding this study to include more DPSC isolates with variable expression of these pluripotency biomarkers will provide substantial information that could validate the findings of the current study. In addition, a more comprehensive evaluation of other potential biomarkers, such as non-coding microRNA, may provide more specific and targeted methods for bioengineering and biotechnology applications utilizing DPSC [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that lncRNA can regulate the expression of miRNA and play a role in tumorigenesis [15].…”
Section: Introductionmentioning
confidence: 99%